Heal or no heel: Outcomes of ischaemic heel ulcers following lower limb revascularization from a multi‐ethnic Asian Cohort in Singapore. Issue 6 (24th August 2020) - Linn, Yun Le; Chan, Sze Ling; Soon, Shereen Xue Yun; Yap, Charyl Jia Qi; Lim, Mervin Nathan Han Hui; Lee, Qing Wei Shaun; Chong, Tze Tec; Tang, Tjun Yip
Abstract: Ischaemic diabetic heel ulcers are difficult to treat and prognosis is often guarded. The aim was to document our outcome of treating heel ulcers following revascularization in a predominantly diabetic Asian cohort presenting with chronic limb threatening ischaemia from Singapore. Retrospective cohort study (n = 66, 66 limbs) over a 5‐year period. Data were collected from hospital electronic health records. Outcomes included time to healing, amputation free survival (AFS), and mortality. Minimum follow‐up period was 6 months. Multivariate regression analysis was performed to look for factors associated with poor outcome. Mean age was 67.4 ± 8.8 years. 62/66 (93.9%) were diabetics. Mean wound size at presentation was 3.6 ± 2.3 cm. Mean Wound, Ischaemia, Foot Infection (WIFI) score was 5 ± 1.6. 12/66 (18%) patients had a patent posterior tibial artery pre‐operatively. Straight line flow was restored in only 31/66 (46.9) patients but 47/66 (71.2%) had successful limb salvage. Median time to wound healing was 90.0 (IQR 60‐180) days. A median of 1 (IQR 0‐2) wound debridement was required. Patients who underwent negative pressure dressing (23/66; 34.8%) required a median of 26 (IQR 13‐33) cycles to achieve healing. Amputation free survival (AFS) was 72% and 68% at 6‐ and 12‐months, respectively. Mortality rate was 16.7% and 19.7% at 6‐ and 12‐months, respectively. Low albumin level and initial Rutherford class were independent predictors of worse 6‐month AFS. Outcomes of heel ulcers post revascularisation may not be as poor as previously described. Persistent attention to wound care with multidisciplinary effort is needed for optimal healing.